2021
DOI: 10.3390/medicina57050473
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Disorders in Children with Inflammatory Bowel Disease

Abstract: Background and Objectives: Inflammatory bowel disease (IBD) is a chronic condition and mainly affects the intestines, however, the involvement of the other organs of the gastrointestinal tract (upper part, pancreas, and liver) have been observed. The coexistence of IBD with pancreatic pathology is rare, however, it has been diagnosed more frequently during recent years in the pediatric population. This article reviews the current literature on the most common pancreatic diseases associated with IBD in the pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Pancreatitis in children remains a poorly understood condition despite increasing incidence and risk of morbidity and mortality 8–10 . The aetiology of the disease is variable and management remains inconsistent among practitioners 9,11–13 . In most paediatric cases, AP resolves and patients have no further complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatitis in children remains a poorly understood condition despite increasing incidence and risk of morbidity and mortality 8–10 . The aetiology of the disease is variable and management remains inconsistent among practitioners 9,11–13 . In most paediatric cases, AP resolves and patients have no further complications.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The aetiology of the disease is variable and management remains inconsistent among practitioners. 9,[11][12][13] In most paediatric cases,…”
Section: Discussionmentioning
confidence: 99%
“…It initiates antigen-specific mucosal immune responses against bacterial invasion into intestinal epithelial cells. Indeed, it has been demonstrated that GP2-deficient colitis mice present a more severe intestinal inflammation and an enhanced E. coli population than healthy mice, proving the role of GP2 in preventing E. Coli mucosal attachment and penetration [ 47 , 48 ]. By contrast, an increase of GP2 expression in the pancreas has been observed in a chemically induced colitis in mice, as a consequence of the production of pro-inflammatory cytokines such as TNF.…”
Section: Role Of Genetics In Pediatric Pancreatitis and Its Association With Ibdmentioning
confidence: 99%
“…By contrast, an increase of GP2 expression in the pancreas has been observed in a chemically induced colitis in mice, as a consequence of the production of pro-inflammatory cytokines such as TNF. A rise in fecal GP2 concentration along with the presence of anti-GP2 antibodies has been also observed in CD patients, although the exact role of pancreatic GP2 and the pathogenetic role of anti-GP2 antibodies in IBD patients remains unclear [ 47 , 48 ].…”
Section: Role Of Genetics In Pediatric Pancreatitis and Its Association With Ibdmentioning
confidence: 99%
See 1 more Smart Citation